Odpowiedź:
[tex]1)\\b^2=a^2+c^2-2ac*cos\alpha\\b^2=10^2+6^2-2*10*6*\frac{1}{2}\\b^2=100+36-60\\b^2=76\\b=\sqrt{76}\\b=2\sqrt{19}\\\frac{a}{sin\beta}=\frac{b}{sin\alpha}\\\frac{10}{sin\beta}=\frac{2\sqrt{19}}{sin60}\\\frac{10}{sin\beta}=\frac{2\sqrt{19}}{\frac{\sqrt3}{2}}\\sin\beta=\frac{5\sqrt3}{2\sqrt{19}}\\sin\beta=\frac{5\sqrt{57}}{38}\\sin\beta\approx0,9934\\\beta=83^o\\\gamma=180-60-83=37^o\\\\[/tex]
[tex]2)\\a^2=6^2+4^2-2*6*4*\frac{\sqrt{2} }{2}\\a^2=36+16-24\sqrt2\\a^2=52-24\sqrt2 \\a^2=4(13-6\sqrt2)\\a=2\sqrt{13-6\sqrt2)}\\a\approx4,2\\\frac{a}{\sin\gamma}=\frac{c}{\sin\alpha}\\\frac{4,2}{\frac{\sqrt2}{2}} =\frac{4}{\sin\alpha} \\\sin\alpha=\frac{10\sqrt2}{21}\\\sin\alpha\approx0,6714\\\alpha=42^o\\\beta=180-45-42= 93^o[/tex]
Szczegółowe wyjaśnienie: